Clinical outcomes in patients hospitalised with dysmagnesemia in the Northern Territory of Australia: a retrospective, longitudinal data-linkage study - Juhaina Al-Maqbali; Abdullah Al Alawi; Asanga Abeyaratne; Sandawana Majoni; Henrik Falhammar (James Cook University, 2024)
Introduction: Magnesium is an essential cation, and dysmagnesaemia is linked to many poor outcomes. This study aimed to assess the prevalence of dysmagnesaemia and associated health outcomes among hospitalised patients. Methods: This register-based study collected demographic and laboratory data of hospitalised patients from five publicly funded hospitals in the Northern Territory, Australia, between 2008 and 2017. Patients were stratified into five groups based on their initial serum magnesium level at admission and followed up to death or 31 December 2017. Results: A total of 22 293 patients were admitted during the study period. Dysmagnesaemia was present in 31.75% of hospitalised patients, with hypomagnesaemia being more common (29.62%) than hypermagnesaemia (2.13%). Hypomagnesaemia was more prevalent (43.13%) among the Australian First Nations Peoples. All levels of hypomagnesaemia were associated with a longer median length of hospital stay (p<0.001). Also, all levels of hypermagnesaemia were associated with a longer median stay in intensive care units (p<0.001). Patients with severe hypermagnesaemia had increased mortality compared to patients with severe hypomagnesaemia (56.0% v 38.0.0%, p<0.0001). Mortality was increased in both hypomagnesaemia (hazard ratio 1.86, 95% confidence intervaI 1.74-1.99, p<0.001) and hypermagnesaemia (1.78, 1.48-2.19, p<0.001) compared to normomagnesaemia. Conclusion: Dysmagnesaemia was prevalent among hospitalised patients and associated with increased mortality.